Variability In Cone And Seed Characteristics Among Plus Trees Of Blue Pine (Pinus Wallichiana A. B. Jackson) In The Kashmir Himalaya, India - MOHD. ASLAM; ZAFAR A. RESHI; T. O. SIDDIQI (International Journal of Pharma and Bio Sciences, 2010)
Eighty eight plus trees representing the entire distributional range of Pinus wallichiana (Blue pine or Kail ) in Kashmir Himalaya were sampled to determine the extent and nature of variability and character association in eight cone and seed traits. Wide variations were observed in cone weight (28.16-46.0 g), number of seeds/cone (41.6-90.6) and 1000 seed weight (42.0-67.0 g). Genetic coefficient of variation, phenotypic coefficient of variation, heritability estimates and genetic advance were higher for cone length, cone width, cone weight, seed length and seed thickness. Genotypic correlation in all the traits was greater than the phenotypic correlation. Seed thickness exhibited significant variability, heritability and maximum genetic gain (29.44%) followed by cone width and seed width. Cone weight, seed length, seed width and seed thickness showed positive direct effect on 1000 seed weight whereas cone length and cone width showed negative direct and indirect effect on 1000 seed weight. The investigation revealed that cone weight, seeds/cone, seed length and seed thickness are important characters because of their direct effect on 1000 seed weight. Thus, these traits should be given top priority while selecting superior genotypes.